The Efficacy of The Open-Ended Approach in Fostering Students’ Mathematical Conceptual Understanding in Terms of Initial Ability - Rusdian Rifai; Trisnawati Trisnawati; Heryani Heryani; Jaka Wijaya Kusuma; Saran Chantarasri (Jurnal Pendidikan MIPA, 2026)
The low mathematical ability of vocational high school (SMK) students is a strategic problem because mathematics is the foundation of technical competence in the era of the Industrial Revolution 4.0. Various pedagogical innovations have been proposed to overcome this problem, but previous studies have often encountered obstacles in effectively improving the conceptual understanding of students with low Initial Mathematical Ability (KAM). This quasi-experimental study was designed to test the effectiveness of the open-ended approach as an alternative learning method and to investigate the role of KAM as a moderating variable, particularly regarding aspects that have not received attention in vocational education research. The research sample consisted of 72 students in grade XI majoring in Computer and Network Engineering (TKJ), divided into a non-equivalent control group design, with the experimental group receiving open-ended approach learning (N=36) and the control group receiving conventional learning (N=36). Data collection was conducted using a mathematics concept comprehension test instrument and an observation sheet for the implementation of learning. Statistical analysis was conducted using the Kruskal-Wallis H test on the normalized N-Gain scores. The results show a significant difference in conceptual understanding between the two groups, with the experimental group's N-Gain score (0.72; high category) statistically higher than the control group's (0.62; medium category). These findings contribute to the literature by demonstrating that the open approach not only improves average academic achievement but also reduces the learning gap through differential mechanisms responsive to heterogeneity in initial abilities. Thus, this study recommends the Open Approach as a pedagogical framework with the potential to transform vocational mathematics learning practices toward a more equitable and adaptive system. Keywords: initial mathematical ability, open-ended approach, conceptual understanding ability.